Skeletal Muscle Fatigue in Slow and Fast Muscles of Type 2 Diabetic Sprague Dawley Rats - Mehvish Ashfaq , Kamil Asghar Imam , Bushra Riaz, Mehvish Ashfaq , Kamil Asghar Imam , Bushra Riaz (Journal of Rawalpindi Medical College, 2017)
Background: To evaluate the effects of type 2 diabetes mellitus on fatigability of soleus (slow) and extensor digitorium longus (EDL) (fast) muscles of female Sprague Dawley rats. Methods:Twenty healthy female Sprague Dawley rats were divided into 2 groups with 10 rats each. Group I (control) was fed with normal diet and group II (diabetic) was given high fat diet. Group II was given intra-peritoneal streptozotocin(STZ) (35mg/kg body weight) on 15th day. Body weight, blood glucose and TG:HDL ratio were estimated on 21st day to confirm type 2 diabetes mellitus (T2DM) induction. Soleus and extensor digitorium longus (EDL) muscles were removed intact and fixed in organ bath system containing Krebs-Ringer buffer solution and connected to data acquisition unit (iWorx®) to study their contractile and fatigability parameters. Results: Soleus and extensor digotorium longus muscles of female diabetic rats displayed significantly (p<0.05) increased fatigability. Conclusions:Fatigability of slow (soleus) and fast (EDL) muscles increases in T2DM.There occurs reduction in resistance to and recovery from fatigue in both slow and fast skeletal muscles of type 2 diabetic female Sprague Dawley rats